Verifying the effective application of the HACCP system in some bottled water plants in the Eastern Province of the Kingdom of Saudi Arabia - Aljalisi, Turki Abdullah; Madkour, Mohamed Hussein; Abd El-Razik, Mohamed Moustafa (Journal of agricultural, environmental and veterinary sciences, 2021)
This study aims to verify the efficiency and effectiveness of applying the HACCP system in bottled water factories. A comparison was made between the factories that implement the HACCP system and the factories that do not implement the HACCP system. In this research، the chemical and bacteriological properties of bottled drinking water in the Eastern Province of the Kingdom of Saudi Arabia were studied. The pH، dissolved solids، nitrates، and fluoride were analyzed. Total coliforms، faecal coliforms، Escherichia coli، and pseudomonas. The results of the chemical analyzes indicated that they are in compliance with the standard limits stipulated in the Saudi Standard for Bottled Drinking Water, where the results of the chemical analysis of the factories were not applied to the HACCP system until the pH ranges between (6-7، 7). 71)، total dissolved solids (122-239) ppm، Nitrates (0،01-2،77) ppm، fluoride (0.01-1.05) ppm، while the results of factories applying HACCP system As follows: pH (6،93-7،34) total dissolved salts (168-197) parts per million، nitrates (0،004-0،42) parts per million، Fluoride (0.94-1،2) ppm. The microbiological results were within the limits allowed for the factories not applied and applied to HACCP system except in one sample for the factories that apply the HACCP system، as the analyzes showed a non-conformity to one of the water samples analyzed due to the presence of pseudomonas bacteria. The researcher presented appropriate recommendations and solutions، including continuous chemical and microbiological analyzes، while checking and reviewing HACCP system in bottled water factories.